PSYCHOLOGICAL CONDITIONS FOR THE SUCCESS IN ADULT FOREIGN LANGUAGE LEARNING TAKING INTO ACCOUNT COGNITIVE STYLES - Smagliy, T.I.; Kudritskaya, M.I.; Silenko, Ye.A. (publisher of Kostanay state pedagogical university, 2020)
This article discusses the importance of cognitive styles in teaching adults foreign languages. The psychological conditions of the formative experiment that contribute to the success of training are described. The results of experimental work with adults throughout the language course are provided. Revealing the characteristics of cognitive styles, the authors analyze the results from their consideration in educational activities under certain psychological conditions, and also reveal the success of adult learning.
Keywords: psychological conditions; adults; learning success; foreign language; cognitive style